COGS Accuracy Strategy in the Food & Beverage Business Model (Study at Hakui Café, Tulungagung) - Isyrohil Muyassaroh; Dhiya’u Shidiqy; Della Puspita; Nabila Riski Laili Pertiwi; Mahamadaree Waeno; Rahman Arifin (Institut Agama Islam Negeri (IAIN) Curup, 2026)
Purpose: The Paper aims to determine the strategy for implementing production cost management and setting selling prices at Cafe Hakui 0 Km Tulungagung. Design/Method/Approach: This study uses a descriptive analysis. It implemented a quantitative non-statistical approach with emphasis on numbers, from data collection and analysis to data presentation. This research was conducted at Cafe Hakui Kopi, located at 0 Km Tulungagung, Tamanan Village, Tulungagung District, Tulungagung Regency. Findings: The results of this study confirm that the production costs and selling prices at Hakui Kopi Km 0 Tulungagung for the